Updated Experience of Mycobacterium chimaera Infection: Diagnosis and Management in a Tertiary Care Center. (1st July 2021) - Tan, Nicholas Y; Tarabochia, Alex D; DeSimone, Daniel C; DeSimone, Christopher V; Wilson, John W; Bagameri, Gabor; Bennett, Courtney E; Abu Saleh, Omar M
Abstract: Background: Despite safety communications from the Food and Drug Administration (FDA) regarding the outbreak of Mycobacterium chimaera infections (MCIs) from contaminated heater-cooler devices, new cases continue to be identified. Methods: We retrospectively reviewed confirmed cases of MCI that were managed at Mayo Clinic sites (Arizona, Florida, and Minnesota) from 09/2015 to 01/2021. Clinical histories including prior cardiovascular surgery were recorded. Diagnostic workup including ophthalmologic examination, imaging, and laboratory testing was reviewed. Treatment and survival outcomes on follow-up were obtained. Results: Twelve patients with MCI were included. All patients had aortic valve or graft replacement. Five patients had their surgical procedures following the 10/15/2015 FDA safety communication. The mean time from surgery to symptom onset (range) was 32 (13–73) months. Ten of 11 patients who underwent ophthalmologic examination had chorioretinal abnormalities. Three patients who underwent microbial cell-free deoxyribonucleic acid sequencing tested positive for M. chimaera, which was subsequently confirmed with blood culture growth. Echocardiography and positron emission tomography/computed tomography (PET/CT) revealed evidence of prosthetic valve/graft infection in 7/12 (58.3%) and 6/10 (60.0%) of cases, respectively. Seven patients (58.3%) underwent redo cardiovascular surgery. Of these, 1 patient died 2 days postdischarge, 1 experienced spinal osteomyelitis relapse, and another had interval prosthetic valve fluorodeoxyglucose (FDG) uptake on PET/CT suspicious for recurrent infection. Among 4 patients on medical therapy only, 3 expired or transitioned to hospice during follow-up. Conclusions: MCI continues to occur despite the FDA communications. Incorporation of ophthalmologic examination and use of advanced tools may improve MCI diagnosis. The mortality in these patients is high even with aggressive surgical/medical management.